50 world's greatest short stories - Pushkin, Alexander 1739-1837. Alexander Sergeyevich Pushkin; Bierce, Ambrose 1842-[1914].; Chekhov, Anton 1860-1904.; Dickens, Charles 1812-1870.; Poe, Edgar Allen 1809-1849.; Fitzgerald, Scott 1896-1940. Francis Scott Key Fitzgerald; Stockton, Frank 1832-1902.; Dostoevsky, Fyodor 1821-1881.; Maupassants, Guy de 1850-1893.; Wells, H.G. 1866-1946. Herbert George Wells; Munro, H. H. Saki 1870-1916. Hector Hugh Munro; London, Jack 1876-1916. John Griffith Chaney; et al. (New Delhi : Prakash Books, 2022)
Discover the best of short fiction in this collectable edition featuring fifty of the greatest stories from around the world. This exquisite collection showcases a curated selection of timeless short stories from renowned authors across the globe. With its beautiful design and captivating narratives, this collectible edition is a treasure for literature enthusiasts.